2022
DOI: 10.3389/fmicb.2022.1065780
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese herbs complex ameliorates gut microbiota dysbiosis induced by intermittent cold exposure in female rats

Abstract: Cold is a common source of stress in the alpine areas of northern China. It affects the microbial community, resulting in the invasion of pathogenic microorganisms and intestinal diseases. In recent years, studies have reported that Chinese herbal extracts and their fermentation broth have a significant beneficial effect on gut microbiota. This study aimed to investigate the probiotic effect of a self-designed Chinese herbs complex on the gut microbiota of rats exposed to cold. The rats were treated with inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Elusimicrobium is usually regarded as probiotic bacteria, which was reported to improve the dysbiosis of intestinal flora and restore intestinal barrier function in rats ( Shi et al, 2017 ). Previous studies have shown that the relative abundance of probiotic Elusimicrobium and Parasutterella were pronouncedly increased in rats treated with Chinese herbs complex, which further improved intestinal health ( Jin et al, 2022 ). Although dietary supplementation of BL can regulate microflora balance in cecal contents of Peking ducks and broilers ( Kan et al, 2021 ; Li et al, 2022 ), the effect of BL on the increased Elusimicrobium and Parasutterella of broilers was not reported and the potential mechanism needs more work.…”
Section: Discussionmentioning
confidence: 97%
“…Elusimicrobium is usually regarded as probiotic bacteria, which was reported to improve the dysbiosis of intestinal flora and restore intestinal barrier function in rats ( Shi et al, 2017 ). Previous studies have shown that the relative abundance of probiotic Elusimicrobium and Parasutterella were pronouncedly increased in rats treated with Chinese herbs complex, which further improved intestinal health ( Jin et al, 2022 ). Although dietary supplementation of BL can regulate microflora balance in cecal contents of Peking ducks and broilers ( Kan et al, 2021 ; Li et al, 2022 ), the effect of BL on the increased Elusimicrobium and Parasutterella of broilers was not reported and the potential mechanism needs more work.…”
Section: Discussionmentioning
confidence: 97%